1999
DOI: 10.1083/jcb.147.4.699
|View full text |Cite
|
Sign up to set email alerts
|

Division versus Fusion: Dnm1p and Fzo1p Antagonistically Regulate Mitochondrial Shape

Abstract: In yeast, mitochondrial division and fusion are highly regulated during growth, mating and sporulation, yet the mechanisms controlling these activities are unknown. Using a novel screen, we isolated mutants in which mitochondria lose their normal structure, and instead form a large network of interconnected tubules. These mutants, which appear defective in mitochondrial division, all carried mutations in DNM1, a dynamin-related protein that localizes to mitochondria. We also isolated mutants containing numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
535
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 480 publications
(567 citation statements)
references
References 27 publications
30
535
1
1
Order By: Relevance
“…In yeast, selective inhibition of either processes significantly modifies mitochondrial size and interconnectivity [23,24]. Among the best-known proteins involved in mitochondrial dynamics are Fzo/mitofusin, a transmembrane GTPase involved in fusion [25], and Dnm1p/dynamin-related protein 1, a dynamin-related protein involved in fission [26].…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, selective inhibition of either processes significantly modifies mitochondrial size and interconnectivity [23,24]. Among the best-known proteins involved in mitochondrial dynamics are Fzo/mitofusin, a transmembrane GTPase involved in fusion [25], and Dnm1p/dynamin-related protein 1, a dynamin-related protein involved in fission [26].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies (described above) suggested that loss of Dnm1p function blocked mitochondrial fission but allowed the fusion of mitochondrial tips to continue, resulting in the formation of elaborate net-like structures [9,10]. Most importantly, the mitochondrial fragmentation induced by a fzo1 mutation no longer occurred in cells containing a dnm1 mutation [9,10].…”
Section: Fission and The Outer Membrane Gtpase Dnm1pmentioning
confidence: 99%
“…The fission and fusion of the inner and outer mitochondrial membranes occur in tandem, although the mechanisms by which this coordination is accomplished are not understood. Fission can occur within a tubule or at a branchpoint in the reticulum and is regulated by a GTPase called Dnm1p [8][9][10]. Fusion always occurs between two mitochondrial tips or between the tip and the side of a tubule, and is regulated by the transmembrane GTPase Fzo1p [11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Drp1/Dnm1, a dynamin-like GTPase, three other proteins were identified in yeast that are required for normal mitochondrial fission, Fis1, Mdv1/ Net2 and Caf4 (Bleazard et al, 1999;Sesaki and Jensen, 1999;Jensen et al, 2000;Shaw and Nunnari, 2002;Griffin et al, 2005). A critical role for each of these factors in yeast mitochondrial fission is evident from the fact that deletion of any one of them results in fusion of normally tubular mitochondria into continuous nets.…”
Section: 'Day Jobs' For Pro-death Mitochondrial Proteinsmentioning
confidence: 99%